2012
DOI: 10.3892/ijmm.2012.929
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β transcript variants associate with oncogene expression in endometrial cancer

Abstract: Abstract. The human ESR2 gene codes for estrogen receptor β1 and for multiple splice variants, which are suggested to exert distinct functions in the cellular estrogen response. Given that the function of ERβ in endometrial cancer remains unclear, we examined the expression of ERβ1, ERβ2 and various further ERβ transcript variants and their association with selected cancer-related genes in 74 human endometrium samples and endometrial cancer specimens by means of RT-qPCR. Additionally, we knocked down ERβ expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Although ERβ has been suggested to coordinately play an important role in maintaining the normal function of the endometrium together with ERα, the precise physiological roles of ERβ in endometrial function remain unclear [ 33 ]. Similarly, the possible involvement of ERβ in the carcinogenesis of endometrial carcinoma is still being debated [ 5 , 7 , 34 ]. Recently, an abnormal balance between the two ER subtypes was suggested to be involved in carcinogenesis, tumor invasion, and poor clinical outcomes in patients with gynecologic malignant tumors [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ERβ has been suggested to coordinately play an important role in maintaining the normal function of the endometrium together with ERα, the precise physiological roles of ERβ in endometrial function remain unclear [ 33 ]. Similarly, the possible involvement of ERβ in the carcinogenesis of endometrial carcinoma is still being debated [ 5 , 7 , 34 ]. Recently, an abnormal balance between the two ER subtypes was suggested to be involved in carcinogenesis, tumor invasion, and poor clinical outcomes in patients with gynecologic malignant tumors [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ER) α has been reported to play an important role in the development of estrogen-dependent malignant tumors. However, recent studies have proposed that ERβ is also associated with gynecologic malignant tumors [ 5 , 6 ]. Moreover, researchers also demonstrated that the expression of ERβ in endometrial endometrioid carcinoma is greater than that in the normal endometrium [ 5 , 7 ] and that a high ERβ/ERα expression ratio is an independent prognostic marker of survival in patients with endometrial endometrioid carcinoma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER- β expression, though lower than ER- α in most endometrial cancers, may be induced in some tumors, in particular endometrial tumors of a higher grade [28]. Reports suggest that it may inhibit the function of ER- α and/or that it may be a marker for poor outcome [29, 30].…”
Section: Endometrial Cancer As a Hormonally Regulated Diseasementioning
confidence: 99%
“…Reports suggest that it may inhibit the function of ER- α and/or that it may be a marker for poor outcome [29, 30]. However, these data are complicated by the presence of several ER- β splice variants that are differentially associated with tumor grade [28]. …”
Section: Endometrial Cancer As a Hormonally Regulated Diseasementioning
confidence: 99%